Zemplén transesterification: a name reaction that has misled us for 90 years. Issue 3 (9th December 2014) - Ren, Bo; Wang, Meiyan; Liu, Jingyao; Ge, Jiantao; Zhang, Xiaoling; Dong, Hai
Abstract : We demonstrated − OH as the deacylation catalyst in methanol, indicating that the Zemplén condition had been misleading us for almost 90 years. Abstract : We demonstrated that using NaOH and NaOMe in methanol for deacylation are identical, indicating that the Zemplén condition has been misleading us for almost 90 years. The traditional base-catalyzed mechanism cannot be used to explain our results. We propose that H-bond complexes play key roles in the base-catalyzed process, explaining why deacylation in methanol can be catalyzed by hydroxide.